Exploring corporate strategy - Johnson, Gerry (Pearson Education, 2006)
Introduce your students to the latest concepts in strategic thinking with this industry-leading text. Exploring Strategy tackles the biggest issues surrounding the operation, growth, and innovation of organisations. With longer case studies included in the Text & Cases edition your students will gain deeper insight into the manager-way of thinking